1967
DOI: 10.1021/j100863a010
|View full text |Cite
|
Sign up to set email alerts
|

Infrared investigation of the adsorption and surface reactions of the C1 through C4 normal alcohols on γ -alumina

Abstract: Infrared investigations of the adsorption of the Ci through C4 normal alcohols on the surface of 7-alumina in the temperature range from 25 to 500°are described. Three different surface species are observed: physically adsorbed alcohol (I), an alkoxide-like chemisorbed surface species (II), and a carboxylate-like chemisorbed surface species (III), in agreement with previous work by Greenler.2 Mechanisms for these adsorption processes are proposed and supported with mass spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

1968
1968
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(32 citation statements)
references
References 0 publications
4
27
0
1
Order By: Relevance
“…Comparing the IR spectrum of the adsorbed methanol with aluminum methoxide, Greenler has concluded [34] that the surface species formed by the adsorption is probably a methoxide surface compound. In contrast, Kagel has shown [35] that the adsorption of methanol on g-alumina surface is temperature dependent: near room temperature both physisorbed alcohol and chemisorbed alkoxide species are formed. According to Busca et al [36], several chemisorbed species may be found, depending on temperature, one of them corresponding to a bidented species with the OH group of methanol bound to aluminum and oxygen surface atoms.…”
Section: Adsorption Of Methanol On the Alumina Clustermentioning
confidence: 94%
“…Comparing the IR spectrum of the adsorbed methanol with aluminum methoxide, Greenler has concluded [34] that the surface species formed by the adsorption is probably a methoxide surface compound. In contrast, Kagel has shown [35] that the adsorption of methanol on g-alumina surface is temperature dependent: near room temperature both physisorbed alcohol and chemisorbed alkoxide species are formed. According to Busca et al [36], several chemisorbed species may be found, depending on temperature, one of them corresponding to a bidented species with the OH group of methanol bound to aluminum and oxygen surface atoms.…”
Section: Adsorption Of Methanol On the Alumina Clustermentioning
confidence: 94%
“…1, alcohol can chemisorb by reaction of its hydroxyl group with surface hydroxyl groups of the alumina, thus forming a stable alkoxide and releasing water. This mechanism has been proven for different normal and secondary alcohol [12,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 80%
“…However, the presence of adsorbed water on the alumina could also be enough for preventing the alcohol from reacting with the surface hydroxyl groups. Therefore, a second modification procedure, Procedure #2, was checked using vacuum in the permeate side as the activation of alumina is preferentially carried out under vacuum or using an inert gas carrier [17,20,22,24]. This procedure aimed at a double objective.…”
Section: Performance Of the Modified Membranesmentioning
confidence: 99%
“…[46] reported that the formate species decomposes more slowly than methoxy species during CH^OH decomposition on ZnO. The formate species has been reported to withstand temperatures as high as 700 K [104][105][106].…”
Section: _]mentioning
confidence: 99%
“…The methoxide and formate species have always been observed in all the IR studies of CH^OH adsorption on metal oxides [46,66,[104][105][106][107][108].…”
mentioning
confidence: 99%